Effects of goethite on the fractions of Cu, Cd, Pb, P and soil enzyme activity with hydroxyapatite in heavy metal-contaminated soil. Issue 72 (27th September 2017) - Cui, Hongbiao; Yang, Xiong; Xu, Lei; Fan, Yuchao; Yi, Qitao; Li, Ruyan; Zhou, Jing
Abstract : Goethite is of great importance as it affects the migration and transformation of heavy metals and phosphorus. Abstract : Goethite is of great importance as it affects the migration and transformation of heavy metals and phosphorus. To further understand the effect of goethite in soil on the immobilization efficiency of heavy metals and soil biological characteristics with the application of hydroxyapatite (HAP), the fractions of Cu, Cd, Pb, and P and soil enzyme activities were determined. The batch experiments indicated that single 1% HAP or 1% goethite treated soil evidently decreased amount of CaCl2 -extractable, exchangeable fraction of Cu, Cd and Pb, compared to the control, and the treatment transformed the fractions from active to inactive ones. Goethite did not change the immobilization and bioaccessibility of Cu, Cd, and Pb in the presence of HAP. HAP application significantly increases soil resin-P, HCl–P, and residual-P, but goethite plus HAP decreases the labile-P, more pronounced than single HAP treatment. Moreover, soil catalase, urease, and acid phosphatase activities are increased markedly in HAP and composite additives soils. Our results suggest that goethite has little effects on the decreasing availability of heavy metals and the enhancing soil enzyme activities in the presence of HAP, but it decreases soil labile P significantly. These findings can provide important insights into the practical application of phosphate-based amendments for heavy metal-contaminated soils with considerable iron oxides.